La construcción del esquema corporal infantil desde una perspectiva merleaupontyana. La propiocepción como fundamento del accouplement fenomenológico - Buffone, Jesica (2019)
“The Construction of the Children’s Body Schema from a Merleaupontyan Perspective. Proprioception as the Basis of Phenomenological Accouplement”. This paper aims to undertake an analysis of the appropriation Merleau-Ponty makes of the concept of body schema, in order to elucidate the implications it has on his description of the construction of one’s own body in early childhood. Considering that the recognition of others and oneself as a dissociated individuality of the environment is a process that takes place during the first months of a baby’s life, we will explore the role that postural impregnation, proprioception and imagination have in the construction of the body schema at the beginning of the child’s life. Setting out the proprioception as a gateway to the body organization could explain the opening of our schema since the first weeks of life, thus making the action and the others a constituent part of my subjectivity even if this has not been able to organize itself yet.